The hidden costs of PEG-rhG-CSF in autologous stem cell transplantation for newly diagnosed multiple myeloma - Ruiqi Wang; Hao Tian; Zhenxing Zhu; Dan Cong; Yuansong Bai; Wenlong Zhang (Scientific Reports)
Abstract To evaluate the clinical value of polyethylene glycolized recombinant human granulocyte-stimulating factor (PEG-rhG-CSF) for hematopoietic reconstitution after autologous stem cell transplantation (ASCT) in newly diagnosed multiple myeloma (NDMM) patients. This study analyzed data from 70 NDMM patients undergoing ASCT, with 33 receiving PEG-rhG-CSF and 37 receiving rhG-CSF. The median time of neutrophil and platelet engraftment, median transfusions of blood products, treatment-related adverse reactions, long-term hematopoietic reconstitution and economic benefits were compared between the two groups. Both groups had similar median neutrophil engraftment, but PEG-rhG-CSF resulted in slower platelet engraftment (13.7 vs. 11.4 days, p < 0.001), more platelet transfusions (2.9 vs. 1.6 units, p < 0.001), higher incidence of grade ≥ 3 diarrhea (60.6 vs. 29.7%, p = 0.006), longer diarrhea duration (9.0 vs. 5.5 days, p = 0.004), and higher costs (RMB 77,126 vs. RMB 68,361, p = 0.027). PEG-rhG-CSF support post-ASCT in NDMM led to slower platelet engraftment, greater platelet transfusion requirements, increased incidence and duration of severe diarrhea, and greater costs, indicating its potential as an expensive treatment option.